Pendampingan Literasi Digital untuk UMKM : Penerapan Pembayaran Digital dalam Meningkatkan Daya Saing Bisnis - Marsinah Marsinah; Fitria Marisya; Rolia Wahasusmiah; Netti Herawati; Edi Harapan (Jurnal Pengabdian Bersama Masyarakat Indonesia, 2025)
The implementation of digital payments in micro, small, and medium enterprises (MSMEs) in Indonesia is one of the important steps to increase business competitiveness in the digital era. The Community Service Program (PKM) aims to provide digital literacy assistance to MSME actors by focusing on the implementation of digital payment systems, such as e-wallets and QRIS. This activity was carried out by a team of lecturers from Prasetiya Mandiri Polytechnic and PGRI Palembang University, which involved practical training and direct assistance to MSMEs. Through this training, it is hoped that MSME actors can optimize the use of digital payment technology to improve transaction efficiency and expand their market reach. In addition, intensive assistance is also provided to overcome technical obstacles in the implementation of the digital payment system. The results of this program show that MSME actors who participate in this mentoring experience increased understanding and skills in using digital payment technology, which has an impact on increasing the competitiveness and operational efficiency of their businesses. This program also makes a positive contribution to the development of MSMEs that can adapt to technological developments and an increasingly digital market.